2015
DOI: 10.1016/j.ijid.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Redefining risk categories for pneumococcal disease in adults: critical analysis of the evidence

Abstract: The ORs for CAP and IPD of patients with two or more comorbidities, with or without smoking, were found to be similar to the ORs for CAP and IPD described in the literature for patients currently classified as high risk. The potential impact of multiple, stacking comorbidities is underestimated and there is a need for the risk categories for pneumococcal disease to be redefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
0
26
0
4
Order By: Relevance
“…Moore et al found that 76% of the adults with IPD in the USA had an indication for pneumococcal vaccination [16]. While comorbidities that are risk factors for IPD are well recognized and are for the most part indications for vaccination what is not readily recognized is the concept of risk factor stacking [29]. For example, when smoking is added to diabetes, chronic obstructive lung disease, and chronic heart disease the odds ratio for acquisition of IPD increases from 8.5 to >40 [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore et al found that 76% of the adults with IPD in the USA had an indication for pneumococcal vaccination [16]. While comorbidities that are risk factors for IPD are well recognized and are for the most part indications for vaccination what is not readily recognized is the concept of risk factor stacking [29]. For example, when smoking is added to diabetes, chronic obstructive lung disease, and chronic heart disease the odds ratio for acquisition of IPD increases from 8.5 to >40 [29].…”
Section: Discussionmentioning
confidence: 99%
“…While comorbidities that are risk factors for IPD are well recognized and are for the most part indications for vaccination what is not readily recognized is the concept of risk factor stacking [29]. For example, when smoking is added to diabetes, chronic obstructive lung disease, and chronic heart disease the odds ratio for acquisition of IPD increases from 8.5 to >40 [29]. The highest rates of IPD are seen among those who are immunocompromised either by underlying disease or by treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bir arada bulunan ≥2 komorbiditesi olan eriş-kinlerdeki pnömokok hastalığı insidans hızlarının, yüksek risk altında olduğu kabul edilenlerdeki kadar ya da onlardan bile yüksek olduğu gözlenmiştir (26). Benzer biçimde, yayımlan-mış 38 çalışmanın sonuçlarının analizi de "risk altında" olarak kabul edilen ancak diabetes mellitus, kronik kalp hastalığı ve kronik obstrüktif akciğer hastalığı gibi komorbiditelerinin sayısı ≥2 olan hastaları, "yüksek risk" kategorisinde sınıflan-dırmak gerekebileceğini göstermiştir (27). ABD'de 2002-2011 arasında gazilerin başvurduğu tıp merkezlerinde ciddi pnö-mokok infeksiyonu saptanan ≥50 yaşındaki aşısız erişkinler-de, örneğin ≥65 yaşında olma, alkolizm, kronik kalp hastalığı, kronik karaciğer hastalığı, kronik solunum hastalığı, diabetes mellitus, immün yetmezlik ya da tütün kullanımı gibi çok sayı-daki yığılmış risk faktöründen ("stacked risk") altısını birden taşıyanlardaki 30 günlük mortalite, tek bir risk faktörünü taşı-yanlara göre yaklaşık üç kat daha yüksek bulunmuştur (28).…”
Section: Tanımlarunclassified
“…Indeed, in 2014, a total of 952 IPD cases were notified (accounting for 78% of all cases), while cases of invasive diseases caused by Neisseria meningitidis accounted for 163 (13%) and those caused by Haemophilus influenzae accounted for 105 (9%) [4]. The risk of developing IPD is unevenly distributed among different population groups, being significantly higher among young children, the elderly, and people with several underlying medical conditions and health-compromising behaviors [5,6]. …”
Section: Introductionmentioning
confidence: 99%